Impact of contact force sensing technology on outcome of catheter ablation of idiopathic pre-mature ventricular contractions originating from the outflow tracts. Issue 4 (18th November 2020) - Reichlin, Tobias; Baldinger, Samuel H; Pruvot, Etienne; Bisch, Laurence; Ammann, Peter; Altmann, David; Berte, Benjamin; Kobza, Richard; Haegeli, Laurent; Schlatzer, Christian; Mueller, Andreas; Namdar, Mehdi; et al.
Abstract: Aims: Catheter ablation of frequent idiopathic pre-mature ventricular contractions (PVC) is increasingly performed. While potential benefits of contact force (CF)-sensing technology for atrial fibrillation ablation have been assessed in several studies, the impact of CF-sensing on ventricular arrhythmia ablation remains unknown. This study aimed to compare outcomes of idiopathic outflow tract PVC ablation when using standard ablation catheters as opposed to CF-sensing catheters. Methods and results: In a retrospective multi-centre study, unselected patients undergoing catheter ablation of idiopathic outflow tract PVCs between 2013 and 2016 were enrolled. All procedures were performed using irrigated-tip ablation catheters and a 3D electro-anatomical mapping system. Sustained ablation success was defined as a ≥80% reduction of pre-procedural PVC burden determined by 24 h Holter ECG during follow-up. Overall, 218 patients were enrolled (median age 52 years, 51% males). Baseline and procedural data were similar in the standard ablation (24%) and the CF-sensing group (76%). Overall, the median PVC burden decreased from 21% (IQR 10–30%) before ablation to 0.2% (IQR 0–3.0%) after a median follow-up of 2.3 months (IQR 1.4–3.9 months). The rates of both acute (91% vs. 91%, P = 0.94) and sustained success (79% vs. 74%, P = 0.44) were similar in the standard ablation and the CF-sensing groups. No differences were observed in subgroups according to arrhythmia origin from the RVOT (65%) or LVOT (35%). Complications were rare (1.8%) and evenly distributed between the two groups. Conclusion: The use of CF-sensing technology is not associated with increased success rate nor decreased complication rate in idiopathic outflow tract PVC ablation.